Removal of the Antibiotic Amoxicillin from Polluted Freshwater by Biosorption Using the Living Biomass of the Microalga Chlamydomonas reinhardtii - David Fernández; Julio Abalde; Enrique Torres (Toxics, 2025)
The environment is undergoing a constant incorporation of new pollutants, which must be eliminated to avoid toxicity problems. Amoxicillin (AMX) is a widely used antibiotic today, and for this reason, it reaches natural media with the consequent environmental risk. Biosorption is an effective and environmentally friendly solution which can be used for the removal of AMX. In the present study, the properties of the living biomass of the microalga Chlamydomonas reinhardtii were studied to determine the capacity of this biomass to remove AMX. This biomass has demonstrated to have good qualities to remove AMX with a maximum capacity of 12.72 ± 0.57 mg g−1. Light was an important factor in increasing the removal capacity of this living biomass by 35.2%. Although this antibiotic underwent spontaneous degradation (unaffected by light), the presence of the biomass increased the amount removed and the removal rate. The amount removed by this biomass in the presence of light was always higher than the amount lost by spontaneous degradation. The kinetics that best adjusted was pseudo-second order. Maximum removal was obtained at pH 6. A point of zero charge and Fourier transform infrared spectrometry were used to characterize the biomass and study the process.